Dried noodles substitute tempeh flour and mocaf flour (modified cassava flour) with different percentages of cow's milk: Mi kering subtitusi tepung tempe dan mocaf (modified cassava flour) dengan perbedaan persentase susu sapi - Dwi Tunggul Pawoko; Vivi Nuraini; Yannie Asrie Widanti (Fakultas Sains dan Teknologi Unisri, 2025)
Dry noodles are noodles that are marketed in dry form. This noodle, which is also called egg noodle, has a low water content, only about 13%. Made from eggs and wheat flour, Dried noodles are processed by drying in an oven or drying in the sun to dry before being packaged and marketed. Tempeh has the potential to be used as raw material for noodles because it has a high protein content. Tempe is first processed into flour so that it becomes tempeh flour which will be used for making dry noodles. In addition, local raw materials such as mocaf flour and cow's milk are rich in nutrients such as protein content which can meet the protein needs in the body. The purpose of this study was to determine the chemical and organoleptic characteristics of dry noodles from tempeh and mocaf flour with the addition of cow's milk and to determine which noodle formulations produced high protein content. The experimental design was a completely randomized design (CRD) with the first factor being the ratio of tempe flour and mocaf flour (70 : 30, 60 : 40 and 50 : 50) with the addition of cow's milk (50%, 75% and 100%). The results of this study indicate that the dry noodle formulation with the addition of cow's milk is the best based on chemical and organoleptic values is a comparison tempeh flour 50 and mocaf 50 with a percentage of 100% cow's milk. The results obtained were a moisture content of 4.76%, an ash content of 2.63%, a protein content of 21.79%, a carbohydrate content of 70.81%, a fat content of 14.63% and a crude fiber content of 19.14%. Based on the organoleptic value, the ratio of tempe flour is 70 and mocaf 30 with a percentage of 75% cow's milk. The results obtained were 2.80% color, 2.80% aroma, and 2.99% elasticity. This research achieved the desired goal, namely to produce high protein noodles.